Jasmonates are signals in the biosynthesis of secondary metabolites - Pathways, transcription factors and applied aspects - A brief review - Wasternack, Claus; Strnad, Miroslav (New biotechnology, 2019)
Jasmonates (JAs) are signals in plant stress responses and development. One of the first observed and prominent responses to JAs is the induction of biosynthesis of different groups of secondary compounds. Among them are nicotine, isoquinolines, glucosinolates, anthocyanins, benzophenanthridine alkaloids, artemisinin, and terpenoid indole alkaloids (TIAs), such as vinblastine. This brief review describes modes of action of JAs in the biosynthesis of anthocyanins, nicotine, TIAs, glucosinolates and artemisinin. After introducing JA biosynthesis, the central role of the SCFCOI1-JAZ co-receptor complex in JA perception and MYB-type and MYC-type transcription factors is described. Brief comments are provided on primary metabolites as precursors of secondary compounds. Pathways for the biosynthesis of anthocyanin, nicotine, TIAs, glucosinolates and artemisinin are described with an emphasis on JA-dependent transcription factors, which activate or repress the expression of essential genes encoding enzymes in the biosynthesis of these secondary compounds. Applied aspects are discussed using the biotechnological formation of artemisinin as an example of JA-induced biosynthesis of secondary compounds in plant cell factories.
Keywords: artemisininy; Glucosinolates; Plants; Artemisinin; Metabolic Engineering; Biosynthetic Pathways; Terpenoid indole alkaloids; Secologanin Tryptamine Alkaloids; anthokyaniny; Nicotine; Transcription factors; signální transdukce; Oxylipins; regulátory růstu rostlin; oxylipiny; nikotin; Plant Proteins; biosyntetické dráhy; Models, Biological; sekologanin-tryptaminové alkaloidy; Signal Transduction; glukosinoláty; rostliny; Transcription Factors; biologické modely; Artemisinins; Plant Growth Regulators; transkripční faktory; Jasmonate; metabolické inženýrství; Cyclopentanes; Anthocyanins; cyklopentany; rostlinné proteiny